HUBUNGAN DUKUNGAN KELUARGA DAN KEBUTUHAN SPIRITUAL DENGAN TINGKAT KECEMASAN PASIEN GAGAL GINJAL KRONIK DALAM MENJALANI TERAPI HEMODIALISIS DI RSUD BANGKINANG - EKA PUTRI; ALINI ALINI; INDRAWATI INDRAWATI (Universitas Pahlawan Tuanku Tambusai, 2020)
The increasing incidence of kidney failure is due to the epidemiological transformation of the disease in recent years. Chronic renal failure patients undergoing hemodialysis therapy will experience anxiety caused by the threat of death, and do not know the final outcome of the therapy. This study aims to analyze the relationship between family support and spiritual needs with the level of anxiety of chronic kidney failure patients undergoing hemodialysis therapy at Bangkinang Hospital in 2020. This study used a cross sectional research design. The population in this study were 47 patients undergoing hemodialysis therapy in the hemodialysis unit at Bangkinang Hospital. The sample in this study patients who underwent hemodialysis therapy were 47 people with a total sampling technique. Collecting data through distributing questionnaires. Data processing used univariate and bivariate analysis. The results showed most respondents had low family support as many as 25 people (53.2%), most respondents had low spiritual needs as many as 29 people (61.7%), most respondents experienced high anxiety levels as many as 30 people (63, 8%). The results of the Chi-square test found that there was a significant relationship between family support and spiritual needs with the level of anxiety of chronic kidney failure patients undergoing hemodialysis therapy at Bangkinang Hospital. It is recommended that the hospital be able to provide counseling about family support and spiritual needs in order to reduce the anxiety level of chronic kidney failure patients.